Regulation of Public Finances in Hungary in Light of Financial Constitutionality - Nagy, Zoltán (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
The first section of this chapter presents the historical development and theoretical division of financial law. The fundamental legal institutions of modern financial law are widely regulated in the Hungarian Fundamental Law. Public finance constitutionality is an important area of financial jurisprudence. Based on the fundamental law regulations, certain areas of financial jurisprudence are presented in each section: public finances, financial and asset management, the system of public burden bearing and public burdens, public asset management, and the monetary system. The presentation of the basic legal institutions of the constitutionality of public finances allows the reader to get an overview of the Hungarian system of financial law.KEYWORDS: Constitutionality of public finances, constitutional law of finance, public finances, budget, financial law, asset management, public burdens, taxation.